Genetic Liability, Environment, and the Development of Fussiness in Toddlers: The Roles of Maternal Depression and Parental Responsiveness - Natsuaki, Misaki N. (2010)
Using a longitudinal, prospective adoption design, this study examined the effects of the environment (adoptive parents’ depressive symptoms and responsiveness) and genetic liability of maternal depression (inferred by birth mothers’ major depressive disorder [MDD]) on the development of fussiness between 9 and 18 months of age in adopted children. The sample included 281 families linked through adoption, with each family including four individuals (i.e., adopted child, birth mother, adoptive father and mother). Results showed that adoptive mothers’ depressive symptoms at 9 months of child age were positively associated with child fussiness at 18 months of age. A significant interaction between birth mothers’ MDD and adoptive mothers’ responsiveness indicated that children of birth mothers with MDD showed higher levels of fussiness at 18 months of age when adoptive mothers had been less responsive at 9 months of child age. However, in the context of high levels of adoptive mothers’ responsiveness, children of birth mothers with MDD did not show elevated fussiness at 18 months. Findings are discussed in terms of gene-environment interactions in the intergenerational risk transmission of depression.